Simulation of film bulk acoustic resonator based on two-dimensional phononic crystals - Linhao SHI; Weipeng XUAN; Lingling SUN; Shurong DONG; Hao JIN; Jikui LUO (物联网学报)
A new structure of film bulk acoustic resonator (FBAR) based on phononic crystal (PnC) was proposed.The phononic crystal was used as the acoustic reflection layer at the bottom of the bulk acoustic wave resonator, which has the characteristics of high reflectivity and low transmittance of elastic wave in its band gap.The band gap characteristics of four kinds of phononic crystals with different structures were calculated by the finite element software COMSOL Multiphysics.The main conclusions are as follows.If the bulk acoustic resonator is working within the band gap of the phononic crystal, PnC can be used as the bottom acoustic reflection layer of the FBAR.With using PnC as the acoustic energy reflect structure, the impedance curve of FBAR is smooth, and the quality factor is closed to traditional FBAR with a value of 859 and effective mechanical coupling coefficient of 6.32%.